2016
DOI: 10.3791/53588
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Model of Biomimetically Breathing Pulmonary Acinar Airways

Abstract: Quantifying respiratory flow characteristics in the pulmonary acinar depths and how they influence inhaled aerosol transport is critical towards optimizing drug inhalation techniques as well as predicting deposition patterns of potentially toxic airborne particles in the pulmonary alveoli. Here, soft-lithography techniques are used to fabricate complex acinar-like airway structures at the truthful anatomical length-scales that reproduce physiological acinar flow phenomena in an optically accessible system. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Based on the microfluidic technology, human alveoli-on-a-chip was built to study the fluid flow and particle transport and deposition. Sznitman’s group [ 30 , 31 , 32 , 33 ] developed a 5-generation alveolar chip in real size. By controlling the pressure in the surrounding chambers, the periodical expansion and contraction of the channel wall was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the microfluidic technology, human alveoli-on-a-chip was built to study the fluid flow and particle transport and deposition. Sznitman’s group [ 30 , 31 , 32 , 33 ] developed a 5-generation alveolar chip in real size. By controlling the pressure in the surrounding chambers, the periodical expansion and contraction of the channel wall was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Benam et al used this technology to test smoking and non-smoking conditions, and confirmed that using the lung-on-a-chip yielded experimental results that were closer to clinical physiological and inflammatory reactions compared with those from animal experiments, and previously undiscovered biomarkers that were even more accurate were found and analyzed (Benam et al, 2016a). At the same time, other teams have developed lung chip models with different design structures and physiological responses (Fishler et al, 2015;Fishler and Sznitman, 2016;Humayun et al, 2018;Stucki et al, 2018;Khalid et al, 2020). The lung-on-a-chip have been developed to demonstrate their importance in drug development and disease models, but still have several practical challenges must be overcome if such devices are to be used in toxicology research and application (Low and Tagle, 2017;Wu et al, 2020).…”
Section: Lung-on-a-chipmentioning
confidence: 94%
“…Unlike traditional microfluidic devices that require stacking multiple PDMS molds, they proposed a simple method for manufacturing the top cavity by embedding the syringe barrel partly into the PDMS mold. This novel design can provide physiological respiratory movement, which generates airflow similar to that under physiological conditions [ 54 , 55 ]. In addition, Katan et al designed a chip to study the flow topology in the fetal lung at the embryonic stage, reproducing the true proportions of the fetal airway in three different pregnancy stages and revealing the unique flow patterns at different stages of fetal life [ 56 ].…”
Section: Physiological Model Of Respiratory System Based On Organ-on-a-chipmentioning
confidence: 99%